Modern Sports Dentistry (Textbooks in Contemporary Dentistry,, 2018)
This book is intended as a one-stop reference that will assist primary care community dentists, sports physicians, athletic trainers, and emergency room physicians in meeting the needs of athletes when managing facial and dental trauma and sports-related oral diseases. The opening chapters provide a complete review of sports-related dentoalveolar trauma, with coverage of emergent care, the role of endodontics, surgical issues, and restorative considerations. Prevention of dental trauma by means of mouthguards is then examined, with attention to materials and design, public policy concerning the use of mouthguards, and the role of mouthguards in relation to the ever more pressing issue of concussion in sport. Dental erosion in athletes, for example due to energy drinks, is discussed, as are the possible sequelae of use of spit tobacco, performance-enhancing drugs, and ergogenic aids. The new topic of the potential value of dental appliances in enhancing sports performance is also addressed. The book concludes by reviewing the role of the dentist within the multidisciplinary sports medicine team. The text is supported by an abundance of informative illustrations.